A Multi-Criteria Approach and Sustainability Index as a Consideration on Torpedo scad Fisheries Management in Sunda Strait - Yonvitner Yonvitner; Mennofatria Boer; Vera Ardelia (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsThe main problem to ensure the good management in fisheries was multi species fishPrecautionary approach needed to get a good view of the important criteria in fisheries managementNeeded a multi criteria and index to make a final conclusion of the any criteriaNatural history and population dynamic parameter important input to sustainability indexValidation model in sunda strait as preliminary approach will help to get a good data and resultAbstractTorpedo scad species known are both economic and ecologic important pelagic fish that fishing catch tends to increase last a few decades. For sustainability, in the long term, needed a management strategy that complies with measurable fish population indicators. This effort is a part of the precautionary approach in fiseries management in related exploitation. This research was conducted in Labuan fishing port performed for more than 8 months and then analyzed with population parameters. Composite analysis by multi-criteria approaches found that the average score of Torpedo scad is 1.48 and then grouped as moderate sustainability. Schooling fish, including torpedo scad has been moderate until high sustainability levels. Overall population status in this area refer to moderate potential risk and needs a precautionary approach on management.